Características clínicas e laboratoriais do fígado em alcoolistas idosos e não idosos - Borini, Paulo; Guimarães, Romeu Cardoso; Calamita, Zamir (Saúde e Pesquisa, 2019)
The medical bibliography is deficient in research involving structural and laboratory abnormalities of the liver in asymptomatic and oligosymptomatic male alcoholics. The present study describes the alterations in tests that evaluate liver aggression, lesion and dysfunction, also correlating these with the changes in the consistency and sensitivity of the liver in aged and non-aged alcoholics. Cross-sectional study involving 100 alcoholic men, 50 aged and 50 non-aged. Of the aged and non-aged, respectively, the liver was palpable in 68% and 80%, the spleen was percutable in 72% and 74% and palpable in 12% and 22%, non-painful soft hepatomegaly was observed in 14% and 8%, painful hepatomegaly in 0% and 2%, firm hepatomegaly (painful and non-painful) in 54% and 70%, hepatomegaly and splenomegaly (percutable and palpable spleen) in 84% and 84%, and portal hypertension in 10 % and 14%. Elevated levels of aspartate aminotransferase were observed in 66% and 84%, alanine aminotransferase in 24% and 60%, gamma glutamyl transferase in 46% and 82% and alkaline phosphatase in 0% and 16% of the aged and non-aged, respectively. Elevation of aspartate aminotransferase greater than twice the reference value and the ratio aspartate aminotransferase to alanine aminotransferase greater than 2 were observed in 18% and 42% and 18% and 10% of the aged and non-aged, respectively. Hypoalbuminemia and hyperbilirubinemia were observed in 70% and 24% of the aged and 40% and 44% of the non-aged, respectively. The clinical and laboratory alterations observed are compatible with acute liver disease in 18% and 42%; chronic liver disease in 54% and 70%; portal hypertension in 10% and 14% of aged and non-aged patients, respectively.